Travel Time Reduction Due to Infrastructure Development in Hungary - Berta, Tamas; Török, Ádám (Promet - Traffic&Transportation, 2012)
The main scope of this paper is to present the formulation and visualization of shortening travel time in road transport due to the improvement of road network in Hungary. The formulation of the travel time based model has been developed by the authors. The paper also presents the demonstration of the results. The approach followed is quite innovatory in terms of visualization. The travel times were taken into account as opposed to geographical distances. Also, graph theory is used in order to calculate the matrix of “travel time” distances. The data from more than 30 cities were included in the model so as to make it quite representative for Hungary. KEYWORDS: road transportation, reduction of travel time, positive external effect